Risk of acute coronary syndrome and relationship with the use of khat and tobacco products in the Jazan region, Saudi Arabia: A prospective case-control study - Rashad Alsanosy; Mohamed Salih Mahfouz; Abdulelah Mohammed Arishi; Siddig Ibrahim Abdelwahab; Manal Taha; Osama Albasheer; Hasan Mohammed Daghriri; Khalid Ahmed Majrashi; Abdullah Farasani; Ahmed A. A. Altraifi; Isameldin E. Medani; Nasser Hakami (Tobacco Induced Diseases)
Introduction Previous studies have identified several risk factors for acute coronary syndrome (ACS). This study was intended to examine the potential risk of ACS associated with khat and tobacco use.